2017
DOI: 10.1016/j.virol.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol reducing agents inhibit assembly of type I parainfluenza viruses

Abstract: Many enveloped RNA viruses utilize lipid rafts for the assembly of progeny virions, but the role of cholesterol, a major component of rafts, on paramyxovirus budding and virion formation is controversial. In this study, we analyzed the effects of FDA-approved cholesterol-reducing agents, gemfibrozil and lovastatin, on raft formation and assembly of human parainfluenza virus type 1 (hPIV1) and Sendai virus (SeV). Treatment of the human airway epithelial A549 cells with the agents, especially when combined, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 48 publications
5
41
0
Order By: Relevance
“…1B). These results indicate that cholesterol reducing agents are effective in blocking infectious virus production of IAV and RSV similar to hPIV1, as we previously reported (Bajimaya et al, 2017). …”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…1B). These results indicate that cholesterol reducing agents are effective in blocking infectious virus production of IAV and RSV similar to hPIV1, as we previously reported (Bajimaya et al, 2017). …”
Section: Resultssupporting
confidence: 88%
“…Cells treated with Gem (400 μM) and Lov (40 μM) for 24 h were infected with the viruses at MOI of 0.5 for 24 h. Cells were then fixed and the number of infected cells were determined by immunostaining using specific anti-NP monoclonal antibodies (mAb). We did not detect any difference in the number of infected cells, even though cellular cholesterol was reduced by 20% by both agents at 24 h (Bajimaya et al, 2017). These data suggested that reduced infectious virus production was not due to limited initial infection (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations